2021
DOI: 10.1186/s43055-021-00547-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated rhino-orbital mucormycosis (CAROM)—a case report

Abstract: Background There has been a rapid rise in the number of COVID-19-associated rhino-orbital mucormycosis (CAROM) cases especially in South Asian countries, to an extent that it has been considered an epidemic among the COVID-19 patients in India. As of May 13, 2021, 101 CAROM cases have been reported, of which 82 cases were from India and 19 from the rest of the world. On the other hand, pulmonary mucormycosis associated with COVID-19 has a much lesser reported incidence of only 7% of the total C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…DM was also present in the majority of the patients with COVID-19-associated mucormycosis reported in the literature. 4,5,14,15 In our study, 2 of 8 patients were diagnosed with COVID-19-associated mucormycosis within 2 months of COVID-19 infection, 4 patients were diagnosed in the third month, 1 patient after 5 months, and 1 patient after 160 days of COVID-19 infection. Various surgical procedures that were performed in each of these patient as a part of the management protocol included bilateral (B/L) maxillectomy along with an alveolar process and hard palate removal (patient 1); B/L infrastructure maxillectomy þ B/L frontal sinusotomy (patient 2); right maxillectomy with orbital exenteration (patient 3); B/L maxillectomy involving anterior two-thirds hard palate with B/L frontal and ethmoidal sinusotomy (patient 4); B/L maxillectomy with B/L ethmoidal and maxillary sinusotomy (patient 5); right maxillectomy including alveolar process along with a bony defect wall of the maxillary and frontal sinus with right orbital exenteration (patient 6); right maxillectomy along with removal of the right zygoma, maxillary sinus, and right pterygoid plate (patient 7); and left suprastructure maxillectomy along with orbital exenteration (patient 8).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…DM was also present in the majority of the patients with COVID-19-associated mucormycosis reported in the literature. 4,5,14,15 In our study, 2 of 8 patients were diagnosed with COVID-19-associated mucormycosis within 2 months of COVID-19 infection, 4 patients were diagnosed in the third month, 1 patient after 5 months, and 1 patient after 160 days of COVID-19 infection. Various surgical procedures that were performed in each of these patient as a part of the management protocol included bilateral (B/L) maxillectomy along with an alveolar process and hard palate removal (patient 1); B/L infrastructure maxillectomy þ B/L frontal sinusotomy (patient 2); right maxillectomy with orbital exenteration (patient 3); B/L maxillectomy involving anterior two-thirds hard palate with B/L frontal and ethmoidal sinusotomy (patient 4); B/L maxillectomy with B/L ethmoidal and maxillary sinusotomy (patient 5); right maxillectomy including alveolar process along with a bony defect wall of the maxillary and frontal sinus with right orbital exenteration (patient 6); right maxillectomy along with removal of the right zygoma, maxillary sinus, and right pterygoid plate (patient 7); and left suprastructure maxillectomy along with orbital exenteration (patient 8).…”
Section: Discussionmentioning
confidence: 51%
“…However, in most of the cases of COVID-19-associated mucormycosis reported in the literature, patients were older 50 years. 5,8,14,15 This may be because our study included survivors of COVID-19-associated mucormycosis, who came for reconstructive surgeries after complete resolution of the disease. Mortality rate is higher in COVID-19-associated mucormycosis and chances of survival are higher in younger patients with better immunity and lesser comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are a limited number of published studies concerning CAM diagnosis, we included some case reports in this area. Sethi et al, (Sethi et al, 2021) reported a case report 55-year-old male was admitted in the COVID-19 ICU for a period of 2 weeks and treated according to the existing protocols, including steroids and ventilator therapy. The CT head revealed complete opacification of the right maxillary sinus and anterior ethmoidal air cells with internal foci of air without an air fluid level was appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that SARS-CoV-2 infection may affects CD4+ and CD8+ T cells , causing reduction of absolute number of lymphocytes and T cells associated with creation of a temporary state of compromised immunity [3].…”
Section: Discussionmentioning
confidence: 99%